The Diagnostic Reproducibility of Tomosynthesis for the Correlation between Acromiohumeral Distance and Rotator Cuff Size or Type - Song, Yoonah; Lee, Seunghun; Lee, Bong Gun; Joo, Young Bin; Song, Soon-Young (Korean journal of radiology, 2018)
To correlate the acromiohumeral distance (AHD) using tomosynthesis and rotator cuff (RC) pathology and various anatomical indices and to assess the diagnostic reproducibility of tomosynthesis for the evaluation of subacromial impingement. A retrospective review of 63 patients with clinically suspected subacromial impingement was conducted. Two musculoskeletal radiologists independently measured the following quantitative data: the AHD on plain radiographs and the AHD at three compartments (anterior, middle, and posterior) using tomosynthesis, computed tomography (CT) arthrography, or magnetic resonance (MR) arthrography. To investigate the association between the AHD and RC pathology and various anatomical indices, we reviewed the arthroscopic operation record as the referenced standard. The size of rotator cuff tear (RCT) in full-thickness tears displayed a significant inverse correlation with the middle and the posterior tomosynthetic AHDs ( < 0.05). The results of an ANOVA revealed that the middle tomosynthetic AHD retained a significant association with the type of RCT ( = 0.042), and the posterior tomosynthetic AHD retained significance for the size of RCT in a full-thickness tear ( = 0.024). The inter-modality correlation exhibited significant agreement especially among the plain radiography, tomosynthesis, and CT or MR arthrography ( < 0.05). The intraobserver and interobserver correlation coefficients (ICCs) displayed excellent agreement (ICC = 0.896-0.983). The humeral head diameter and glenoid height were significantly correlated with patient height and weight. Acromiohumeral distance measurement using tomosynthesis is reproducible compared with other modalities.